Digital Marketing and MSMEs Survival Strategy in the E-Commerce Platform Economy: A Systematic Literature Review - Pamungkas, Puntoadji; Dewi, Reni Shinta (Dinasti Publisher, 2026)
This study aims to synthesize current literature on the role of digital marketing strategies, e-commerce, and technological innovation in enhancing the resilience and sustainability of MSMEs. Drawing from a systematic review of 14 international journals, the analysis maps out MSME survival mechanisms through a well-defined strategic sequence. This path begins with strengthening human capital through financial and digital literacy to mitigate the risk of inflated operational costs. The success of this digital transformation heavily relies on developing dynamic organizational capabilities to respond agilely to volatile platform dynamics. At the operational level, short-form video content and omnichannel marketing tactics prove to be the most efficient methods for building brand awareness and customer engagement. Furthermore, leveraging e-commerce platforms alongside a strong entrepreneurial orientation serves as the primary driver for business growth and long-term financial viability during economic disruptions. This study concludes that digitalization is not merely the adoption of technical tools, but rather the construction of integrated internal capabilities. Management readiness and infrastructure support are critical factors ensuring that digital investments yield a sustainable competitive advantage instead of becoming an operational burden.